First-principles study of photovoltaics and carrier mobility for non-toxic halide perovskite CH3NH3SnCl3: theoretical prediction. Issue 32 (22nd July 2016) - Wang, Lin-Zhi; Zhao, Yu-Qing; Liu, Biao; Wu, Li-Juan; Cai, Meng-Qiu
Abstract : The crystal structures, optical properties and carrier mobility for three phases of non-toxic perovskite halide CH3 NH3 SnCl3 are calculated by applying density functional theory with the nonlocal van der Waals (vdW) correlation. Abstract : Promising candidates in this respect are organometal perovskites ABX3, which have been intensely investigated during the last years. In this paper, we calculate the crystal structures, optical properties and carrier mobility for three phases of non-toxic perovskite halide CH3 NH3 SnCl3 by applying density functional theory with the nonlocal van der Waals (vdW) correlation. The results show that CH3 NH3 SnCl3 has superior performance in terms of its optical absorption coefficient, which reaches as high as 10 5 cm −1 and has proven itself to be a perfect solar light harvester. Most importantly, the results of intrinsic carrier mobility of CH3 NH3 SnCl3 show that the electron mobility of the triclinic phase can achieve a large magnitude of 1700 cm 2 V −1 s −1, which is mainly due to the small effective mass. We ascribe the superior photoelectric property to the ferroelectricity, which may be caused by the distorted octahedral SnCl6 − .